Analysis of Digital Marketing Strategy in Increasing Impulse Purchase of Online Fashion Products through Optimizing Customer Reviews and Price Discounts with Lifestyle as an Intervening Variable - Chalid Imran Musa; Azlan Azhari; Kristina Parinsi (LITERACY : International Scientific Journals of Social, Education, Humanities, 2026)
This research is motivated by the increasing phenomenon of impulsive buying in online fashion products influenced by customer reviews and price discounts in the digital era. The study aims to analyze the effect of customer reviews and price discounts on impulsive buying behavior with lifestyle as an intervening variable. A quantitative approach was applied using a survey method involving 140 respondents who were e-commerce users in Makassar City. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique. The results reveal that customer reviews and price discounts have a positive and significant effect on lifestyle and impulsive buying. Furthermore, lifestyle is proven to mediate the relationship between customer reviews and price discounts toward impulsive buying behavior. The findings indicate that higher quality reviews and more attractive discounts offer strengthen consumers' tendencies to make impulsive purchases. This research contributes to the development of digital marketing strategies by emphasizing the importance of review credibility and price discount programs as key factors influencing consumers' lifestyle patterns and impulsive buying behavior, particularly among younger generations who are active online shoppers in the e-commerce era.